Exploring Internal Ribosome Entry Sites as Therapeutic Targets - Komar, Anton A.; Hatzoglou, Maria (Frontiers in Oncology, 2015)
Initiation of eukaryotic mRNA translation may proceed via several different routes, each requiring a different subset of factors and relying on different and specific interactions between the mRNA and the ribosome. Two modes predominate: (i) so-called cap-dependent initiation, which requires all canonical initiation factors and is responsible for about 95-97% of all initiation events in eukaryotic cells; and (ii) cap-independent internal initiation, which requires a reduced subset of initiation factors and accounts for up to 5% of the remaining initiation events. Internal initiation relies on the presence of so-called Internal Ribosome Entry Site (IRES) elements in the 5’ UTRs of some viral and cellular mRNAs. These elements (often possessing complex secondary and tertiary structures) promote efficient interaction of the mRNA with the 40S ribosome and allow for internal ribosome entry. Internal initiation of translation of specific mRNAs may contribute to development of severe disease and pathological states, such as hepatitis C and cancer. Therefore, this cellular mechanism represents an attractive target for pharmacological modulation. The purpose of this review is to provide insight into current strategies used to target viral and cellular IRESs and discuss the physiological consequences (and potential therapeutic implications) of abrogation/modulation of IRES-mediated translation.